Log(4w+8)=log(2w-9)

Simple and best practice solution for Log(4w+8)=log(2w-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Log(4w+8)=log(2w-9) equation:


Simplifying
Log(4w + 8) = log(2w + -9)

Reorder the terms:
goL(8 + 4w) = log(2w + -9)
(8 * goL + 4w * goL) = log(2w + -9)
(8goL + 4gowL) = log(2w + -9)

Reorder the terms:
8goL + 4gowL = glo(-9 + 2w)
8goL + 4gowL = (-9 * glo + 2w * glo)
8goL + 4gowL = (-9glo + 2glow)

Solving
8goL + 4gowL = -9glo + 2glow

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '9glo' to each side of the equation.
8goL + 9glo + 4gowL = -9glo + 9glo + 2glow

Reorder the terms:
9glo + 8goL + 4gowL = -9glo + 9glo + 2glow

Combine like terms: -9glo + 9glo = 0
9glo + 8goL + 4gowL = 0 + 2glow
9glo + 8goL + 4gowL = 2glow

Add '-2glow' to each side of the equation.
9glo + 8goL + -2glow + 4gowL = 2glow + -2glow

Reorder the terms:
9glo + -2glow + 8goL + 4gowL = 2glow + -2glow

Combine like terms: 2glow + -2glow = 0
9glo + -2glow + 8goL + 4gowL = 0

Factor out the Greatest Common Factor (GCF), 'go'.
go(9l + -2lw + 8L + 4wL) = 0

Subproblem 1

Set the factor 'go' equal to zero and attempt to solve: Simplifying go = 0 Solving go = 0 Move all terms containing g to the left, all other terms to the right. Simplifying go = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(9l + -2lw + 8L + 4wL)' equal to zero and attempt to solve: Simplifying 9l + -2lw + 8L + 4wL = 0 Reorder the terms: 8L + 9l + -2lw + 4wL = 0 Solving 8L + 9l + -2lw + 4wL = 0 Move all terms containing g to the left, all other terms to the right. Add '-8L' to each side of the equation. 8L + 9l + -2lw + -8L + 4wL = 0 + -8L Reorder the terms: 8L + -8L + 9l + -2lw + 4wL = 0 + -8L Combine like terms: 8L + -8L = 0 0 + 9l + -2lw + 4wL = 0 + -8L 9l + -2lw + 4wL = 0 + -8L Remove the zero: 9l + -2lw + 4wL = -8L Add '-9l' to each side of the equation. 9l + -2lw + -9l + 4wL = -8L + -9l Reorder the terms: 9l + -9l + -2lw + 4wL = -8L + -9l Combine like terms: 9l + -9l = 0 0 + -2lw + 4wL = -8L + -9l -2lw + 4wL = -8L + -9l Add '2lw' to each side of the equation. -2lw + 2lw + 4wL = -8L + -9l + 2lw Combine like terms: -2lw + 2lw = 0 0 + 4wL = -8L + -9l + 2lw 4wL = -8L + -9l + 2lw Add '-4wL' to each side of the equation. 4wL + -4wL = -8L + -9l + 2lw + -4wL Combine like terms: 4wL + -4wL = 0 0 = -8L + -9l + 2lw + -4wL Simplifying 0 = -8L + -9l + 2lw + -4wL The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| -4x+9y=15 | | ln(9)=4x | | -8r^2=72 | | 15x^2-65x+60=0 | | -80/16 | | .8x+.25(80)=.4(120) | | .5(x+20)+1.3x=91 | | -203=-7(-7x-20) | | 70/25 | | 12x+4y+17x-y+90=180 | | 6-5y=2y-8 | | 7/2x-1=2 | | K/3-5=8 | | 2.6=1.9+s | | 4a^2+33a+8=0 | | (3x+79)+y=180 | | 33=3(2p+3) | | .8(x+40)+x=113 | | 6-2(2x-4)=38 | | -3x+7(x+5)=5x-5 | | -5(x+5)+4=-21 | | 6-p=-5 | | 2x+7-2x-4= | | ln(2x)-1=0 | | -0.10(22)+0.45x=0.05(x-12) | | 15+11x= | | 1161=-9(-10x+31) | | 17.75x+24=18.95x+18 | | 6a+2=3a+a | | 4x-3=27+x | | 6y=-8x-1 | | 0.17y+0.07(y+7000)=1690 |

Equations solver categories